2016
DOI: 10.1039/c6ta01347c
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoparticles spaced 3D graphene films for binder-free lithium-storing electrodes

Abstract: Using a copper nanoparticle-spaced graphene film as the anode, a newly developed lithium-ion battery exhibits a high charge/discharge capacity, an excellent reversibility, a high coulombic efficiency, and a good rate capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…In order to understand, the appropriate reasons behind the above influenced behaviour of properties, it is much needed to study the solidification and organization of metallic material in a confined region between graphene sheets. Reported studies [14][15][16] suggest that the metal atoms make a sheathing organization over the graphene substrate during the processing of nano-composite systems. The utmost interface area between the metal -matrix and graphene substrate enhance the strength of the metal-matrix graphene composite against during external load applications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand, the appropriate reasons behind the above influenced behaviour of properties, it is much needed to study the solidification and organization of metallic material in a confined region between graphene sheets. Reported studies [14][15][16] suggest that the metal atoms make a sheathing organization over the graphene substrate during the processing of nano-composite systems. The utmost interface area between the metal -matrix and graphene substrate enhance the strength of the metal-matrix graphene composite against during external load applications.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported to date [9][10][11][12][13][14][15][16][17][18][19][20] suggest that metal atoms make a sheathing arrangement on the graphene surface. The maximum contact area between the metal matrix and graphene during the metal sheathing process enhances the strength of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Electrolyte ion migration drives the electromechanical response of IPMC actuators, and thus electrochemical behaviors would affect their electromechanical performance. To analyze the electrochemical behaviors, the EIS spectra of PVDF family IPMCs in water and IL environments were measured (Figure ).…”
Section: Resultsmentioning
confidence: 99%